Exploring social influences and values in promoting sustainable food consumption using hybrid three stage methods - Yanhong Wu; Jianqiang Yu (Scientific Reports)
Abstract Although social media is widely recognized as necessary for promoting sustainable food consumption, the theoretical essence of its social influence has yet to be clarified. This research establishes a mutually beneficial model for sustainable food consumption, drawing on Social Influence Theory and Value Theory. The study collected data from an online survey of 15 experts in sustainable food and 311 consumers and analyzed it through a hybrid three-stage approach of fuzzy Delphi, PLS-SEM, and ANN. The results indicate that subjective norms, group norms, and social identity positively influence egoistic and altruistic values, promoting sustainable food consumption. In comparison, social identity has a more important impact on sustainable food consumption, followed by subjective norms and group norms. Usage and value barriers are the main obstacles to sustainable consumption in China, with value barriers moderating the relationship between altruistic value and sustainable food consumption. This study offers innovative approaches to leveraging information technology for achieving sustainable development goals. It holds substantial practical value for stakeholders, including food marketers, government policymakers, and social advocates, providing actionable insights into optimizing marketing strategies, implementing policy incentives, and promoting a culture of sustainable food consumption.